English student teachers' constraints during their teaching internship programs with the English Department of FKIP at Unsyiah in Aceh - Salviana Salviana; Asnawi Muslem; Bukhari Daud (Universitas Syiah Kuala, 2018)
Teaching internship programs are designed to smooth the transition from student to teacher. At the same time the teaching internship assignment gives the teacher training institutions an opportunity to evaluate the teaching capabilities of their soon-to-graduate students. It is one of the most important components of the teacher training program; an opportunity for student teachers to put their theoretical studies into practice. The objective of this study was to investigate the constraints faced by student teachers during their teaching internship programs. A qualitative method was employed in this study, which involved 26 students from the 2016/2017 teaching internship program at the Faculty of Teacher Training and Education, University of Syiah Kuala. A convenient random sampling technique was used to select the sample and a questionnaire was used as the instrument to collect the data which was analyzed using the Miles and Huberman method. Based on the results there were fourteen constraints faced by the student teachers during their teaching internship programs. The constraints were mainly in the domains of personal matters, class participation, class management, instructional methods, emotional issues, adjusting to students and quality of supervision. As teaching practice is an important component of a teacher training program, considerable attention must be given to make it highly effective and fruitful. Therefore, this study suggests that more co-operation from the faculty and the schools is needed in terms of supervision to improve and optimize the outcomes from this program.